2013
DOI: 10.1177/0042098013477697
|View full text |Cite
|
Sign up to set email alerts
|

Residential Segregation, Spatial Mismatch and Economic Growth across US Metropolitan Areas

Abstract: Numerous studies have demonstrated the detrimental influence of residential segregation on poor inner-city residents. This study examines the impact of residential segregation on the welfare of populations in US metropolitan areas using economic growth as the indicator. Panel data of US metropolitan areas spanning 25 years, 1980-2005, are used to analyse the effect of segregation on economic growth. The results show that both racial and skill segregation have a negative impact on shortand long-term economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 77 publications
(82 reference statements)
1
45
1
Order By: Relevance
“…Residential segregation has long been a subject of inquiry by urban geographers and sociologists (Fossett & Waren, 2005;, and its related demographic dynamics may complicate patterns of neighborhood change and segregation (Wyly, 1999). Residential segregation is linked to multiple dimensions of inequality including inadequate education, poor health, and lack of jobs (Li, Campbell, & Fernandez, 2013;Wei, Xiao, Simon, Liu, & Ni, 2018;Williams & Collins, 2001). Segregation is a significant societal concern and is central to the study of urban inequality in cities in the United States, and increasingly in Europe and developing countries as well.…”
Section: Intra-urban Dynamics Of Inequality: Residential Segregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Residential segregation has long been a subject of inquiry by urban geographers and sociologists (Fossett & Waren, 2005;, and its related demographic dynamics may complicate patterns of neighborhood change and segregation (Wyly, 1999). Residential segregation is linked to multiple dimensions of inequality including inadequate education, poor health, and lack of jobs (Li, Campbell, & Fernandez, 2013;Wei, Xiao, Simon, Liu, & Ni, 2018;Williams & Collins, 2001). Segregation is a significant societal concern and is central to the study of urban inequality in cities in the United States, and increasingly in Europe and developing countries as well.…”
Section: Intra-urban Dynamics Of Inequality: Residential Segregationmentioning
confidence: 99%
“…Such segregation has negative effects on skill-based or knowledge-based urban growth. Except for the typical results of residential segregation such as limited access to job information and networks and low upward mobility, the isolation of low-skilled workers also decreases the productivity of high-skilled workers because they also have low accessibility to the services they demand (Li et al, 2013).…”
Section: Intra-urban Dynamics Of Inequality: Residential Segregationmentioning
confidence: 99%
“…Proximity and geographic access to employment is another indicator of residents' economic opportunity and demonstrates the spatial mismatch that exists in many urban areas (Li, Campbell, & Fernandez, 2013;Stoll, 2005 Reflects, in part, neighborhood economic resources and ability to invest in educational resources for local students (Kenyon, 2007) Poverty ACS, 2008ACS, -2012 High poverty is related to the uneven distribution of economic resources. Studies have indicated that high poverty is correlated also with poor health and educational outcomes (D. Berliner, 2006;D.…”
Section: Major Companiesmentioning
confidence: 99%
“…The dispersed cities have less established mass transit infrastructure than the compact cities. The poor are more likely to live in the urban areas due to more employment opportunities, however, remain unemployed due to the transport and related issues [23,24]. The future studies should analyze data by zip codes and states to compare the impact of distances in urban areas in seeking healthcare with accessible versus not so accessible mass transit system.…”
Section: Discussionmentioning
confidence: 99%